Analogue IC design the current-mode approach - Toumazou, C. (Chris).; Lidgey, F. J. (John).; Haigh, D. G. (David). (London, United Kingdom Institution of Engineering and Technology, 1990)
The book covers the following areas: analogue integrated circuit design; current-mode circuit; current conveyor; current-mode analogue amplifier; high frequency CMOS transconductor; bipolar current mirror; dynamic current mirror; continuous-time filter; switched capacitor monolithic filter; LCR filter simulation; current variable; charge variable; switched-current filter; analog interface circuit; current-mode A/D converter; current-mode D/A converter; current-copier circuit; current feedback; voltage amplifier; neural network building block; and analog MOS VLSI.
Also available in print version.
Electronic reproduction.
Keywords: Electronic circuit design; Linear integrated circuits -- Design and construction; Electronic books